Differences in Vasa Vasorum Distribution in Human Aortic Aneurysms and Atheromas. (July 2022) - Sano, Masaki; Sasaki, Takeshi; Baba, Satoshi; Inuzuka, Kazunori; Katahashi, Kazuto; Kayama, Takafumi; Yamanaka, Yuta; Tsuyuki, Hajime; Endo, Yusuke; Sato, Kohji; Takeuchi, Hiroya; Unno, Naoki
The pathophysiological difference between aortic atheromas and aneurysms is unknown. We focused on the vasa vasorum (VV), which play a critical role in maintaining aortic homeostasis and are also involved in vascular diseases. We investigated the differences in VV between the atheromas and aneurysms. Human abdominal aortic samples were obtained from patients with abdominal aortic aneurysm during surgery or autopsy cases. Autopsy cases were divided into 2 groups according to atheromas. The VV were evaluated using immunohistochemical staining for von Willebrand factor. Intimal VV increased in both the atheroma and aneurysm groups, medial VV increased, and adventitial VV decreased only in the aneurysm group. We also observed that the medial VV were connected to the adventitial VV in the atheroma group and to intimal VV in the aneurysm group. We suggest the outside-in VV or inside-out VV theories. Atheroma induces hypoxia of aortic walls, and angiogenic factors might induce an increase of intimal VV derived from adventitial VV (outside-in VV). However, adventitial VV decrease induces hypoxia of aortic walls, and angiogenic factors might induce an increase of intimal VV derived from aortic lumen (inside-out VV). These differences of VV may contribute in elucidating the pathophysiology of aortic diseases.